Overview of update training records in workforce development unit, Sarawak Chief Minister department/ Magdeline Janan Lincoln - Lincoln, Magdeline Janan (2015)
In this chapter, it will discuss more about the whole job description which relates with the daily tasks and routine in the work place. On the other hand, it will also review about the past and present job description and at the same time will focus on job analysis in the current organisation. As we know, job description will includes all responsibilities, roles and personal skills required in performing a task in the organisation. Listed in the table below is the current job description as an Assistant Administrative Officer in Workforce Department Unit (WDU) and also the previous experience in Public Relation Unit (PRU) in Lands and Surveys Department.